2016
DOI: 10.1007/s10544-016-0062-2
|View full text |Cite
|
Sign up to set email alerts
|

c-Jun N-terminal kinase-dependent apoptotic photocytotoxicity of solvent exchange-prepared curcumin nanoparticles

Abstract: Indian spice curcumin is known for its anticancer properties, but the anticancer mechanisms of nanoparticulate curcumin have not been completely elucidated. We here investigated the in vitro anticancer effect of blue light (470 nm, 1 W)-irradiated curcumin nanoparticles prepared by tetrahydrofuran/water solvent exchange, using U251 glioma, B16 melanoma, and H460 lung cancer cells as targets. The size of curcumin nanocrystals was approximately 250 nm, while photoexcitation induced their oxidation and partial ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…Numerous reports showed its anticancer effects or antibacterial activity . In our previous research, we established that curcumin nanoparticles produced by solvent exchange method are phototoxic upon blue light irradiation (λ = 470 nm) toward three cell lines (U251 glioma, B16 melanoma, and H460 lung cancer cells) . The phototoxicity of curcumin nanoparticles depended on irradiation time and curcumin concentration.…”
Section: Introductionmentioning
confidence: 95%
“…Numerous reports showed its anticancer effects or antibacterial activity . In our previous research, we established that curcumin nanoparticles produced by solvent exchange method are phototoxic upon blue light irradiation (λ = 470 nm) toward three cell lines (U251 glioma, B16 melanoma, and H460 lung cancer cells) . The phototoxicity of curcumin nanoparticles depended on irradiation time and curcumin concentration.…”
Section: Introductionmentioning
confidence: 95%
“…19 It shows a remarkable range of pharmacological activity, including antioxidant, anti-inammatory and anticancer activity as well antibacterial. [20][21][22][23][24][25][26][27] Paunović et al found that photoexcited nanocurcumin displayed a signicant cytotoxicity depending both on the irradiation time and nanocurcumin concentration. 26 In the absence of blue light irradiation nanocurcumin displayed very small cytotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…High levels of ROS are toxic for cell membrane, protein, and genetic material (Fakhri, Abbaszadeh, Dargahi, & Jorjani, 2018). Induction of oxidative stress via elevating ROS generation is advantageous in cancer therapy (Pelicano, Carney, & Huang, 2004). This is due to the efficacy of ROS in the stimulation of mitochondrial-and endoplasmic reticulum (ER)-mediated apoptosis (Prag, Kula-Alwar et al, 2020;.…”
Section: Curcumin and Apoptosismentioning
confidence: 99%